Functionalization of liposomes: microscopical methods for preformulative screening. (June 2015) - Belletti, Daniela; Vandelli, Maria Angela; Tonelli, Massimo; Zapparoli, Mauro; Forni, Flavio; Tosi, Giovanni; Ruozi, Barbara
Abstract The development of smart delivery systems able to deliver and target a drug to the site of action is one of the major challenges in the field of pharmaceutical technology. The surface modification of nanocarriers, such as liposomes, is widely investigated either for increasing the blood circulation time (by pegylation) or for interacting with specific tissues or cells (by conjugation of a selective ligand as a monoclonal antibody, mAb). Microscopical analysis thereby is a useful approach to evaluate the morphology and the size owing to resolution and versatility in defining either surface modification or the architecture and the internal structure of liposomes. This contribution aims to connect the outputs obtained by transmission electron (TEM) and atomic force (AFM) microscopical techniques for identifying the modifications on the liposomal surface. To reach this objective, we prepared liposomes applying two different pegylation technologies and further modifying the surface by mAb conjugation. This work demonstrates the feasibility to apply the combined approach (TEM and AFM analysis) in the evaluation of the efficacy of a surface engineering process.